2020
DOI: 10.1186/s12864-020-6507-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles of Dunaliella salina in response to hypersaline stress

Abstract: Background: Dunaliella salina is a good model organism for studying salt stress. In order to have a global understanding of the expression profiles of Dunaliella salina in response to hypersaline stress, we performed quantitative transcriptomic analysis of Dunaliella salina under hypersaline stress (2.5 M NaCl) of different time duration by the second and third generation sequencing method. Results: Functional enrichment of the up-regulated genes was used to analyze the expression profiles. The enrichment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 63 publications
5
26
1
Order By: Relevance
“…Taken together, the results of this study indicate that AS forms have regulatory functions and may diversify the functions of the DsMEK1 gene in D. salina. [41,42]. For transformation and selection experiments solid and liquid De Walne's medium were employed, and adjusted to contain a final concentration of 0.5 M NaCl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the results of this study indicate that AS forms have regulatory functions and may diversify the functions of the DsMEK1 gene in D. salina. [41,42]. For transformation and selection experiments solid and liquid De Walne's medium were employed, and adjusted to contain a final concentration of 0.5 M NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…D. salina CCAP (1952-5) was provided by the Freshwater Algae Culture Collection of the Institute of Hydrobiology, Wuhan, China. The culture was maintained in De Walne’s medium and cultivated at 25 °C and 40 μmol m −2 s −1 provided by cool-white fluorescent lamps, under a 16/8 h light/dark cycle with various NaCl concentrations (1.5 M and 3.5 M) and 0.4 mM H 2 O 2 [ 41 , 42 ]. For transformation and selection experiments solid and liquid De Walne’s medium were employed, and adjusted to contain a final concentration of 0.5 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…It is apparent that several pathways and processes with connection to different mechanisms are contributed to salt stress responses of D. salina . Previously transcriptome analysis, which solely has been focused on DEGs identification showed that “post-translational modifications”, “signal transduction mechanisms”; “translation, ribosomal structure, and biogenesis”; and “RNA processing and modification” similarly enriched in both types of analyses 6 , 25 . Although, systems biology approach applied here rediscovered these processes as responsive mechanisms; however, our analysis showed that some processes such as “sulfur-based metabolisms” and “Proteasome” distinctively enriched in non-preserved modules.…”
Section: Discussionmentioning
confidence: 99%
“…Expressed sequence tag (EST) profiling of D. salina in hypersaline condition also identified 1401 unique responsive transcripts were contributed in protein synthesis, energy, primary metabolism, and protein fate 5 . Moreover, a recent global transcriptome sequencing showed that enhancements of photosynthesis and biosynthesis of porphyrins, as well as degradation of starch, synthesis of glycerol, membrane lipid desaturation, are taken part in D.salina responses to hypersaline conditions 6 . Hovewer, due to the complexity of salt stresses responding processes in microalgae, underlying molecular mechanisms for salt stress response in microalgae remain a daunting challenge 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Unialgal strains, culture conditions and growth patterns D. salina CCAP (1952-5) was provided by the Freshwater Algae Culture Collection of the Institute of Hydrobiology, Wuhan, China. The culture was maintained in De Walne's medium and cultivated at 25 C and 40 μmol m −2 s −1 provided by cool-white fluorescent lamps, under a 16/8 h light/dark cycle with various NaCl concentrations (1.5 M and 3.5 M) and 0.4 mM H 2 O 2[41,42]. For transformation and selection experiments solid and liquid De Walne's medium were employed, and adjusted to contain a final concentration of 0.5 M NaCl.…”
mentioning
confidence: 99%